The Influence of Motivation and Work Environment on Performance (Study on Dental Profession Program at RSGM UNPAD) - Mamta Vasandani; Hendrati Dwi Mulyaningsih; Muhardi Muhardi (Research Synergy Foundation, 2025)
The performance of dental professional program students in dental education hospital is essential for ensuring high quality healthcare services and developing clinical competencies. Their level of performance also has direct implications for patient safety and the quality of dental care delivered. This study analyzes the level of motivation, work environment conditions, and performance of dental professional program students, as well as the partial and simultaneous effects of motivation and the work environment on their performance at the Dental and Oral Hospital, Padjadjaran University. Using a quantitative descriptive approach, data were collected through survery involving 125 respondents selected through stratified random sampling. Motivation was assessed through achievement, affiliation, and power needs, while the work environment included physical and non-physical aspects. The results show that dental professional program students demonstrated good motivation, whereas the overall work environment was rated poor, especially in physical conditions. Their performance was generally good in quality, teamwork, responsibility, and initiative, although work quantity remained low. Regression analysis revealed that motivation and work environment had a positive and significant effect on performance, jointly explaining 51.3% of its variability. These findings indicate that strengthening motivation and improving physical work conditions are essential to enhance the performance of dental professional program students, which may ultimately improve patient care quality and clinical education outcomes. Beyond these findings, the study offers broader theoretical and practical contributions by highlighting how educational environment and organizational factors shape health professional training, providing insights that can inform hospital management and the design of more effective clinical education systems.